Manifestations of Dual Religiosity among Bemba Catholics: Beliefs and Practices within Indigenous Supernatural Cosmology in Muchinga Province, Zambia - Armstrong Chanda; Austin Mumba Cheyeka; Tomaida Milingo (Journal of Multidisciplinary Science: MIKAILALSYS, 2026)
Although dual religiosity has received increasing scholarly attention, its implications for religious identity and practice among Catholics in contemporary Zambia remain insufficiently understood. This study examines the manifestation of dual religiosity among Bemba Catholics in Muchinga Province, Zambia, with particular attention to beliefs and practices shaped by African Indigenous Religion (AIR) cosmology of supernatural powers and Catholicism. Using a hermeneutic phenomenological approach, data were collected from 20 Bemba Catholics and four Catholic priests through interviews, observations, and focus group discussions. The findings indicate that dual religiosity among Bemba Catholics is reflected both in belief systems and in the performance of religious duties, particularly through interpretations shaped by AIR spiritual, supernatural, and magical worldviews. Participants maintained belief in God and spiritual intermediaries, viewed divine punishment as a consequence of wrongdoing, and recognised oaths, vows, and covenants as binding religious and moral commitments. The findings also show deep reverence for ancestors alongside continued engagement with practices associated with witchcraft, sorcery, magic, divination, witch-hunting, traditional healing, and the use of traditional medicines. The study concludes that African traditional beliefs continue to influence the religious practices of African Christians, shaping how Catholic identity is understood and enacted in local contexts. Its contribution lies in clarifying how dual religiosity operates within Bemba Catholic communities and in highlighting the need for church leaders to develop context-sensitive pastoral assistance programmes for Catholics who negotiate multiple religious commitments. The study further encourages ecclesial dialogue on the integration of cultural practices with conversion approaches that respect local traditions while addressing the pastoral challenges of dual religiosity.